Psychometric and clinical assessment of the Persian-SCREENIVF among infertile couples - Masumeh Ghazanfarpour; Tayebeh Mokhtari Sorkhani; Laleh Tajadiny; Fereshteh Zeynivandnezhad; Atefeh Ahmadi; Victoria Habibzadeh; Katayoun Alidousti (Heliyon, 2023)
There is a significant rate of infertility and subsequent psychological problems among couples worldwide. Screening and treatment of the emotional burden of infertility and related Assistant Reproductive Therapies help to improve the quality of life of infertile people. Specific instruments which measure infertility-related status are more accurate. This study aimed to validate the SCREENIVF questionnaire to be used for the psychological screening and care of couples who seek infertility treatment. This quantitative psychometric study was run in infertility private and governmental clinics in XXX on 344 infertile women and men. They filled Persian-SCREENIVF. The Rasch-Andrich rating scale model was applied to investigate the psychometric quality of the survey. Additionally, structural equation modelling was run for model fit and construct validity as well. Moreover, multivariate analysis of variance (MANOVA) was applied to examine the effects of demographic variables on the extracted constructs of the instrument in the population of the study. The results revealed five constructs in the questions with the corresponding items. Overall, the demographic variables have no contribution to these five constructs. Persian-SCREENIVF can be used for further studies about emotional disturbances in infertility problems.